ISOLASI DAN IDENTIFIKASI MIKROORGANISME DALAM ARANG KOMPOS - Sri Komarayati; Ida Indrawait (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
The population and diversity of microorganism in compost charcoal were isolated and identified. The microorganism were prepared in nutrient agar and saboraud agar media. The results revealed that the total population in each gram of compost charcoal were respectively counted 1.78 x 1012 for bacteria and 9.23 x 109 for fungi. Three species of bacteria and fungi were respectively identified; i.e Species II, Bacillus sp and Species V; and Penicillium sp, Fusarium sp and Species A.